Model Pengelolaan Administrasi BK yang Efektif dalam Meningkatkan Mutu Layanan di MA Terpadu Daar Al Hikmah - Binti Ngaliyah (CV. Lentera Literasi Indonesia, 2026)
This study aims to describe and analyze an effective guidance and counseling (BK) administrative management model in improving the quality of school services. Guidance and counseling administration is an important component in supporting the implementation of counseling services in schools because it functions as a system for organizing, documenting, managing, and evaluating various counseling activities. Effective administrative management enables counseling services to be implemented in a structured, systematic, and accountable manner, thereby contributing to the achievement of educational goals and the development of students’ personal, social, academic, and career competencies. This research employed a descriptive qualitative method with a field research approach. The study was conducted at MA Terpadu Daar Al Hikmah Varia Agung, Seputih Mataram. Data were collected through observation, interviews, and documentation. The primary informant in this study was the Vice Principal for Student Affairs, who provided information regarding the implementation of BK administrative management and its role in supporting school services. The collected data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing or verification. The findings indicate that an effective BK administrative management model plays a significant role in improving the quality of school services through several key components. These components include systematic planning, organized record management, accurate student data collection, proper documentation of counseling activities, coordination among school stakeholders, and continuous monitoring and evaluation of counseling programs. The implementation of these components helps ensure that counseling services are delivered efficiently, effectively, and in accordance with students’ needs. Furthermore, well-managed administration facilitates decision-making processes, enhances communication among educational personnel, and supports the achievement of educational objectives.